2002
DOI: 10.1034/j.1600-0889.2002.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and spatial variability in soil CO2 efflux rates for a central Siberian Pinus sylvestris forest

Abstract: Rates of CO2 efflux from the floor of a central Siberian Scots pine (Pinus sylvestris) forest were measured using a dynamic closed chamber system and by a eddy covariance system placed 2.5 m above the forest floor. Measurements were undertaken for a full growing season: from early May to early October 1999. Spatial variability as determined by the chamber measurements showed the rate of CO2 efflux to depend on location, with rates from relatively open areas (“glades”) only being about 50% those observed below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
83
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 59 publications
(79 reference statements)
9
83
0
1
Order By: Relevance
“…Combined correlations of soil respiration between soil temperature and moisture. R s was best predicted by combined models including both T s and W s variables (Davidson et al 1998;Shibistova et al 2002;Epron et al 2004;Jia et al 2006;Chen et al 2013). Epron et al (2004) reported that when W s as a linear variable was added to the temperature variable model, the R 2 of the fitted equations increased from 0.56 to 0.72.…”
Section: The Effect Of T S and W S On Soil Respirationmentioning
confidence: 99%
“…Combined correlations of soil respiration between soil temperature and moisture. R s was best predicted by combined models including both T s and W s variables (Davidson et al 1998;Shibistova et al 2002;Epron et al 2004;Jia et al 2006;Chen et al 2013). Epron et al (2004) reported that when W s as a linear variable was added to the temperature variable model, the R 2 of the fitted equations increased from 0.56 to 0.72.…”
Section: The Effect Of T S and W S On Soil Respirationmentioning
confidence: 99%
“…The multiple linear regression results showed that fine root biomass accounted for the additional spatial variation in R soil that was not explained by SWC and T soil , because AIC and R 2 of the best-fit model including fine rot biomass as an explanatory factor was better for other models without fine root biomass. Fine root biomass often determines the heterogeneity in R soil Katayama et al, 2009;Shibistova et al, 2002 , and fine root biomass often differs with slope position Enoki et al, 1996;Tateno et al, 2004 . Thus, fine root biomass played an important role in understanding the heterogeneity in R soil on a slope.…”
Section: Effect Of Environmental and Biological Factors On R Soilmentioning
confidence: 99%
“…Therefore, it is important to examine the spatial variation in R soil and gather knowledge on how to upscale R soil at a stand scale. R soil is strongly affected by environmental factors, such as soil water content SWC, m 3 m -3 and soil temperature T soil , C, Davidson et al, 1998;Stoyan et al, 2000 . It is also well known that R soil is influenced by biological factors such as fine root biomass Hanson et al, 1993;Shibistova et al, 2002, litter amount Fang et al, 1998 , and microbial biomass Scott-Denton et al, 2003 . These factors, which are potential determinants of R soil , often differ with topography such as slope position e.g., McCarthy and Brown, 2006;Tamai, 2010 , slope aspects e.g., Hanson et al, 1993 , and slope degree e.g., Creed et al, 2013 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, these characteristics might contribute in various ways (e.g. fine root distribution, microbial activity, litter quality and quantity) to the soil respiration of the whole forest (Shibistova et al, 2002;Murphy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%